Art therapy: beading fun and accessible as art inclusive for children with special needs [Art therapy: meronce asik dan nyaman sebagai inklusi seni untuk anak berkebutuhan khusus] - Rusli, Herman; Miranda, Nadhira; Safitri, Nadia; Yahya, Munawwarah; Zhafira, Nanda; Nayutisa, N (Buletin Pengabdian, 2025)
The "MANIS" Program (Meronce Asik dan Nyaman untuk Inklusi Seni Enjoyable and Comfortable Beading for Inclusive Art) was designed to enhance fine motor skills, concentration, and emotional well-being in children with special needs through art therapy centered on beading activities. Guided by the SMART framework (Specific, Measurable, Achievable, Relevant, and Time-bound), the program was structured to ensure clear objectives, measurable outcomes, and practical feasibility. A total of 35 children from the Humeira Special Needs Center participated in the sessions, which also featured a guest facilitator from Beads.Cii, an entrepreneurial outlet specializing in handmade beaded productsintroducing participants to the concept of creative business. Observational data indicated improvements in hand-eye coordination, sustained attention, and creative expression. Moreover, the activities supported emotional regulation and fostered self-confidence among the participants. The programs integration of entrepreneurial elements served as an introduction to creative business opportunities, potentially contributing to future economic empowerment for children with special needs. Evaluation results highlight the programs effectiveness across multiple dimensions, including participant engagement, achievement of therapeutic goals, and the application of entrepreneurship education. The MANIS program offers a promising model for inclusive initiatives that merge art and entrepreneurship as tools for learning and therapeutic development in children with special needs.